Operation of HVDC grids in parallel with AC grids - Ccorimanya, Gustavo Pinares (My University, 2010)
In this thesis, the operation of multi-terminal VSC-HVDC grids is investigated. The advantages of an HVDC grid are the possibility of transporting large amount of power over long distances and the possibility of trading energy among different AC systems. Due to the interest in the exploitation of clean energy sources, far away from consumption center, the idea of using an HVDC grid has become popular in the recent years. The DC voltage of the HVDC system has been identified to be an important parameter analogous to the frequency in AC systems. The variation of DC voltage indicates power unbalance in the DC grid. If the power is sustainably unbalanced, the DC voltage will either increase or decrease. The DC system dynamic, which is very fast, compared with AC system dynamic, demands fast actions; therefore, automatic measures must take place in order to keep the DC system stable. A control strategy, to balance the power in the HVDC system, has been proposed in this thesis. The control strategy proposes that, under contingencies, there is at least one converter that regulates the DC voltage, or in other words, balances power. In order to test the control strategy, a converter model was implemented with the help of the Dynamic Simulation Language (DSL) of SIMPOW. Also, a frequency regulation scheme that emulates machine governors is proposed and further tested in this thesis. The operation of an HVDC grid in parallel with AC grids is tested so that issues such as power oscillations and frequency control can be observed together with the DC grid dynamic. Simulation results show that, with the proposed control strategy, the DC grid remains stable after the simulated outages, even when the converter that regulates the DC voltage is lost. Other important result is that as long as the converters are within its limits, power oscillations don’t disturb the DC system at all. When one converter reaches its current limit and its respective AC system is undergoing power oscillations, they will be reflected in the DC grid and the perturbation could be transferred to another AC system. Also, a proposed frequency regulation scheme is, finally, tested and results show that it is feasible that two selected converters cooperate, effectively, on regulating the frequency in one AC system.
Keywords: Elkraftteknik; Electric power engineering